Pulmonary embolism with chronic obstructive pulmonary disease. Issue 3 (1st September 2021) - Yang, Ruohan; Liu, Guiqing; Deng, Chaosheng
Abstract: Chronic obstructive pulmonary disease (COPD) is a common, preventable, and treatable disease. The incidence of COPD is growing annually in China, and it is a significant and growing public health burden. Multivariate analysis showed that COPD was one of the independent risk factors for the occurrence of pulmonary embolism (PE), and the incidence of PE was significantly higher in COPD patients than in normal subjects. However, PE is often overlooked in patients with acute exacerbation of COPD (AECOPD) because there are many similarities in clinical symptoms between PE and AECOPD, which are difficult to distinguish, resulting in the failure of timely treatment and poor prognosis. Therefore, it is of great significance to understand the clinical manifestations, diagnosis, and treatment of COPD combined with PE for making a more accurate diagnosis, providing timely and effective treatment, and improving the prognosis of such patients.